City Market in Port of Spain - (:unkn) unknown (My University, 2009)
A female vendor standing with her bucket on her head in the Port of Spain market while two young lads look on.
Colour: Yellow, black and white; Style: Portrait; Other: Bordered, Undivided
Keywords: Postcards; Trinidad and Tobago; Women merchants--Trinidad and Tobago; Boys--Trinidad and Tobago; Markets--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago